THE STANDARDS OF THE OFFICIAL DEALER IN THE AUTOMOTIVE BUSINESS - S. Gusev (Publishing House of the State University of Management, 2016)
Disassembled the highlights of the dealer system of identification, peculiarities of regulation of activities of the official dealer of the manufacturer.